Analysis of Number Sense Ability in View of Student Learning Independence - Anggun Badu Kusuma; Fira Nur Setiyana (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2024)
Number sense is an essential skill for mastering the concept of numbers. This study seeks to examine number sense abilities regarding student learning freedom. This research consists of qualitative descriptive research. The research subjects were seventh-grade pupils at SMP Negeri 1 Kebasen in Banyumas. Data were gathered from the learning independence questionnaire, number sense ability test, and interviews. Students were divided into three groups based on their learning independence questionnaire scores: high, medium, and low. The purposive sampling strategy was employed to identify research subjects. The research results show that students with high learning independence are able to fulfill all number sense indicators. Students with moderate learning independence are able to master five number sense indicators. Students with low learning independence are only able to fulfill two indicators.